Prefrontal cortex GABAergic deficits and circuit dysfunction in the pathophysiology and treatment of chronic stress and depression. (April 2017) - Ghosal, Sriparna; Hare, Brendan D.; Duman, Ronald S
Highlights: Chronic stress causes atrophy and decreased connectivity of excitatory neurons in PFC. Stress causes disruption of GABAergic inhibitory neurons in the PFC. GABA subtypes, somatostatin and parvalbumin, are dysregulated by stress. Rapid acting antidepressants inhibit GABAergic interneurons. Abstract : Psychiatric diseases, notably major depression, are associated with imbalance of excitatory and inhibitory neurotransmission within the prefrontal cortex (PFC) and related limbic brain circuitry. In many cases these illnesses are precipitated or exacerbated by chronic stress, which also alters excitatory and inhibitory neurotransmitter systems. Notably, exposure to repeated uncontrollable stress causes persistent changes in the synaptic integrity and function of the principal glutamatergic excitatory neurons in the PFC, characterized by neuronal atrophy and loss of synaptic connections. This can lead to dysfunction of the PFC circuitry that is necessary for execution of adaptive behavioral responses. In addition, an emerging literature shows that chronic stress causes extensive alterations of GABAergic inhibitory circuits in the PFC, leading to the hypothesis that deficits in inhibitory neurotransmission contribute to changes in PFC neuronal excitability and cognitive impairments. Here we review evidence in rodent and human, which points to the mechanisms underlying stress-induced alterations of GABA transmission in the PFC, and its relevance to circuit dysfunction in mood and stress related disorders. These findings suggest that alterations of GABA interneurons and inhibitory neurotransmission play a causal role in the development of stress-related neurobiological illness, and could identify a new line of GABA related therapeutic targets.